Answer:
negative, with slope of -5 and the y-intercept is at 1.
Step-by-step explanation:
Solve each system of equations
12) -2x + 6y = 30
5x + 2y = 10
I really need help.
Answer:
(0,5)
Step-by-step explanation:
-2x+6y=30
5x+2y=10
I'm going to use elimination.
I'm choosing this method because both equations are in the same form.
They are in the form ax+by=c.
So in order to use elimination, I need one of my columns that contain the variables to contain opposites. Neither one of my columns with the variables have that. Example -2x and 5x are not opposites and 6y and 2y are not opposite.
I'm going to multiply both sides of equation 2 by -3. This will help me to achieve the opposites in a column.
So the system becomes:
-2x+6y=30
-15x-6y=-30
---------------------If we add the columns you will see that the variable y get's eliminated. Let's do that.
-2x+6y=30
-15x-6y=-30
-------------------Adding!
-17x+0y=0
-17x =0
x =0
So using one of the equations (you choose; doesn't matter which one you pick) along with x=0, I'm going to find y.
I choose equation 2.
That is I choose 5x+2y=10 along with x=0 to find y.
5x +2y=10 with x=0
5(0)+2y=10
0 +2y =10
2y=10
y=10/2
y=5
The solution is (x,y)=(0,5).
-3x + 3y = 4
-x+ y = 3
Answer:
No solution
Step-by-step explanation:
-3x + 3y = 4
-x + y = 3
Solve the equation for x:
Move the variable to the right side and change its sign
-x + y = 3
-x = 3 - y
Change the signs on both sides of the equation
-x = 3 - y
x = -3 + y
Substitute the given value of x into the equation -3x + 3y = 4
-3x + 3y = 4
x = -3 + y
-3(-3+y)+3y=4
Solve the equation for y
-3(-3+y)+3y=4
y = 0
There is no solution for y.
And since there's no solution for y, the system has no solution.
Slope of the line through the points (2,1) and (4,2) is
Answer:
slope = [tex]\frac{1}{2}[/tex]
Step-by-step explanation:
Calculate the slope m using the slope formula
m = (y₂ - y₁ ) / (x₂ - x₁ )
with (x₁, y₁ ) = (2, 1) and (x₂, y₂ ) = (4, 2)
m = [tex]\frac{2-1}{4-2}[/tex] = [tex]\frac{1}{2}[/tex]
[tex]\huge\boxed{\frac{1}{2}}[/tex]
We can use [tex]\frac{y_2-y_1}{x_2-x_1}[/tex] to find the slope, where [tex](x_1, y_1)[/tex] and [tex](x_2, y_2)[/tex] are both points.
Plug in the values. [tex]\frac{2-1}{4-2}[/tex]
Subtract. [tex]\frac{1}{2}[/tex]
Which represents the solution of the system of equations, y=x^2-x+1 and y=x? Determine the solution set by graphing
Answer:
(1,1)
Step-by-step explanation:
We have the following system:
[tex]y=x^2-x+1[/tex]
[tex]y=x[/tex]
We are going to plug the 2nd equation into the 1st eqaution giving us:
[tex]x=x^2-x+1[/tex]
Now time to solve [tex]x=x^2-x+1[/tex].
[tex]x=x^2-x+1[/tex]
Subtract x on both sides:
[tex]0=x^2-2x+1[/tex]
Now this actually not too bad. This a perfect square trinomial. That is it is of the form [tex]a^2x^2+2abx+b^2[/tex] which equals [tex](ax+b)^2[/tex].
So solving [tex]0=x^2-2x+1[/tex] is equivalent to solving [tex]0=(x-1)^2[/tex]
In order to solve [tex]0=(x-1)^2[/tex], we just need to know when x-1=0 which is at x=1. I got by adding 1 on both sides of x-1=0
Now remember y=x means we have the solution (1,1).
Okay, I'm going to leave all of this algebra here. I'm going to graph this without a graphing calculator.
[tex]y=x[/tex] is a line with slope 1 and y-intercept 0.
[tex]y=x^2-x+1[/tex] is a parabola. The vertex isn't obvious to me right now without the algebra but I do know the parabola is open up because the coefficient of x^2 being positive.
So let's find the vertex.
I'm going to start with the x-coordinate which is -b/(2a).
Compare [tex]x^2-x+1[/tex] to [tex]ax^2+bx+c[/tex] and you should see that [tex]a=1,b=-1,c=1[/tex].
So [tex]-\frac{b}{2a}=-\frac{-1}{2(1)}=\frac{1}{2}[/tex]
So the vertex occurs when the x-coordinate is 1/2.
To find the correspond y-value just use the equation that relations x and y.
That is use [tex]x^2-x+1[/tex].
Replace x with 1/2.
[tex](\frac{1}{2})^2-(\frac{1}{2})+1[/tex]
[tex]\frac{1}{4}-\frac{1}{2}+1[/tex]
Find a common denominator.
[tex]\frac{1}{4}-\frac{2}{4}+\frac{4}{4}[/tex]
[tex]\frac{1-2+4}{4}[/tex]
[tex]\frac{3}{4}[/tex]
So the vertex is at (1/2,3/4) and the parabola is open up.
When you plug in 0 into [tex]x^2-x+1[/tex] you get [tex]0^2-0+1=1[/tex] so the ordered pair (0,1) is on the parabola.
Using symmetry about the line x=1/2 we know that (1,1) is also on this graph.
Let's use this information to produce a graph now.
Now our answer appears to be (1,1) in the graph.
We can check this answer by plugging in (1,1) into our system and see if both equations check out:
[tex]y=x[/tex] gives us 1=1 which is true. So we are good there.
[tex]y=x^2-x+1[/tex] gives us [tex]1=1^2-1+1[/tex] which is true. So we are good there.
The work for showing [tex]1=1^2-1+1[/tex].
[tex]1^2-1+1[/tex]
[tex]1-1+1[/tex]
[tex]0+1[/tex]
1
So the point (1,1) checks out for both of our equations which means it is a common point amongst the equations given.
G(x)=-3x-8
G( )=10
Please help
Answer:
-6 goes inside ( ) since G(-6)=10.
Step-by-step explanation:
It looks like you are looking for a number such that when you put in the ( ) of G( ) you get 10 as a result.
So let's say you are trying to solve G(b)=10 for b.
Well G(x)=-3x-8 so G(b)=-3b-8.
I just replaced all the x's with b's to find G(b).
Now we are trying to solve G(b)=10 for b.
G(b)=10
-3b-8=10
Add 8 on both sides:
-3b=10+8
Simplify:
-3b=18
Divide both sides by -3:
b=18/-3
Simplify:
b=-6
So G(-6)=10!
Check:
-3(-6)-8
18-8
10
G(-6)=10 is confirmed.
-6 goes inside the G( )=10.
answer g(-6)=−3x−8=10
find the mean of the following data:153,140,148,150,142,146,147
Answer:
2.5
Step-by-step explanation:
The positive factors of 12 are 1,2,3,4,6,12
The positive prime factors of 12 are 2 and 3.
(Primes are integer numbers only divisible by themselves and one.)
The arithmetic mean or average of 2 and 3 is (2+3)/2.
(2+3)/2=5/2=2.5
Please help I need answers
Answer:
[tex]-\frac{25}{3}[/tex]
Step-by-step explanation:
To isolate for x, start by multiplying both sides by 2.5.
[tex]\frac{25}{3} =-x[/tex]
Next, divide both sides by -1.
[tex]\frac{-25}{3} =x[/tex]
Answer:
x = -25/3
Step-by-step explanation:
10/3 = x / (-5/2)
Multiply each side by (-5/2) to isolate x
-(5/2) * 10/3 = -5/2 * (x / (-5/2))
-50/6 = x
Divide the top and bottom by 2 on the left hand side
-25/3 =x
Changing to a mixed number ( if required)
3 goes into 25 8 times ( 3*8=24) with 1 left over(25-24=1)
x = -8 1/3
A circle with a radius of 10 inches is placed inside a square with a side length of 20 inches. Find the area of the square.
a. 400
b. 413
c. 314
d. 143
Answer:
The correct answer is option a. 400
Step-by-step explanation:
Points to remember
Area of square = a²
Where 'a' is the side length of square
To find the area of square
It is given that, the side length of square is 20 inches.
Here a = 20 inches
Area = a²
= 20²
= 400
Therefore the correct answer is option a. 400
Find the values of x and y
1-2i/ 2+i + 4-i/3+2i = x+iy
Answer:
[tex]x=\frac{10}{13}[/tex] and [tex]y=-\frac{24}{13}[/tex]
Step-by-step explanation:
The given complex number equation is:
[tex]\frac{1-2i}{2+i}+\frac{4-i}{3+2i}=x+yi[/tex]
We simplify the LHS and compare with the RHS
We collect LCD on the left to get:
[tex]\frac{(1-2i)(3+2i)+(4-i)(2+i)}{(2+i)(3+2i)}=x+yi[/tex]
[tex]\frac{3+2i-6i+4+8+4i-2i+1}{6+4i+3i-2}=x+yi[/tex]
Simplify to get:
[tex]\frac{16-2i}{4+7i}=x+yi[/tex]
Rationalize the LHS:
[tex]\frac{(16-2i)(4-7i)}{(4+7i)(4-7i)}=x+yi[/tex]
Expand the numerator using the distributive property and the denominator using difference of two squares.
[tex]\frac{64-112i-8i-14}{16+49}=x+yi[/tex]
Simplify to get:
[tex]\frac{50-120i}{65}=x+yi[/tex]
[tex]\frac{10-24i}{13}=x+yi[/tex]
[tex]\frac{10}{13}-\frac{24}{13}i=x+yi[/tex]
By comparing real parts and imaginary parts; we have;
[tex]x=\frac{10}{13}[/tex] and [tex]y=-\frac{24}{13}[/tex]
Given that f(x) = x2 + 6x – 2, g(x) = x – 7, and h(x) = x + 4 find each function.
(f + g)(x)
options are
A) x2 + 7x – 9
B) x2 + 7x + 2
C) x2 + 5x – 6
D) x2 + 5x + 5
Answer:
A) x² + 7x - 9
Step-by-step explanation:
Deduct\Add each like-term to arrive at your answer.
What is the volume of the cylinder below?
Answer:
V = π(12²)(15) = 2,160π units³
The correct answer is D.
Which of the following circles lie completely within the fourth quadrant?
Check all that apply.
Answer:
C and D
Step-by-step explanation:
The fourth quadrant is where all the points are in the form (positive, negative).
The center and radius of [tex](x-h)^2+(y-k)^2=r^2[/tex] is (h,k) and r, respectively.
Let's look at the centers and the radius of each of these choices:
A) This one has center (4,-2) and radius [tex]\sqrt{32} \approx 5.7[/tex].
If you add 5.7 to -2 you get a positive number and we needed it negative.
Not this choice; moving on.
B) This one has center (-3,2) and radius [tex]\sqrt{25}=5[/tex].
The center is not even in quadrant 4; moving on.
C) This one has a center (3,-4) and radius 1.
Add 1 to 3 you get 4.
Subtract 1 from 3 you get 2.
Those x's are positive so that looks good so far.
Add 1 to -4 you get -3.
Subtract 1 from -4 you get -5.
Those y's are negative so that looks good.
This circle is in quadrant 4 and doesn't go outside it.
D) This one has center (5,-7) and radius 4.
Add 4 to 5 you get 9.
Subtract 4 from 5 you get 1.
Positive x's is good.
Add 4 to -7 you get -3.
Subtract 4 from -7 you get -11.
Those are negative so that looks good.
[tex](x-3)^{2} +(y+4)^{2} =1[/tex], [tex](x-5)^{2} +(y+7)^{2} =16[/tex] lie completely within the fourth quadrant.
What is fourth quadrant?Quadrant IV: The fourth quadrant is in the bottom right corner of the plane. In this coordinate X has positive values and y has negative values.
According to the question
We have to find the circles lie completely within the fourth quadrant.
Observing the below graph, These two circle lie completely within the fourth quadrant.
[tex](x-3)^{2} +(y+4)^{2} =1[/tex]
[tex](x-5)^{2} +(y+7)^{2} =16[/tex]
These circles lie bottom right corner of the plane.
From the given graphs below Option C and D lie completely within the fourth quadrant.
[tex](x-3)^{2} +(y+4)^{2} =1[/tex], [tex](x-5)^{2} +(y+7)^{2} =16[/tex] lie completely within the fourth quadrant.
Find out more information about fourth quadrant here
brainly.com/question/2364327
#SPJ2
Ellie wants to double her savings of £8000 by investing her money for 16 years.
What interest rate does
she need to look for?
Answer:
She need a interest rate of 6.25%
Step-by-step explanation:
we know that
The simple interest formula is equal to
[tex]A=P(1+rt)[/tex]
where
A is the Final Investment Value
P is the Principal amount of money to be invested
r is the rate of interest
t is Number of Time Periods
in this problem we have
[tex]t=16\ years\\ P=\£8,000\\ A=\£8,000*2=\£16,000\\r=?[/tex]
substitute in the formula above and solve for r
[tex]16,000=8,000(1+16r)[/tex]
[tex]16r=2-1[/tex]
[tex]r=1/16[/tex]
[tex]r=0.0625[/tex]
Convert to percentage
[tex]r=0.0625*100=6.25\%[/tex]
What's the proper name of this quadrilateral?
A. Trapezoid
B. Square
C.Rhombus
D. Parallelogram
Answer:
Trapezoid- A.
Answer:
A. Trapezoid
Step-by-step explanation:
The proper name of this quadrilateral is a trapezoid.
The picture might look confusing because the trapezoid is upside down.
However, it still counts as a trapezoid.
Find the distance between the points (–6, 7) and (0, 8).
Answer:
[tex] \sqrt{37} [/tex]
or 6.08276253
Evaluate the expression when y=6. Y^2-5y-8
Answer:
-2
Step-by-step explanation:
6^2 = 36
5 x 6 = 30
36 - 30 - 8 = -2
Question 2(Multiple Choice Worth 5 points) (08.02 MC)What is the mean absolute deviation for 2, 9, 1, 7, 8, and 9? 1 3 6 8
Answer:
Mean Absolute Deviation = 3.
Step-by-step explanation:
The mean = (2 + 9 + 1 + 7 + 8 + 9) / 6
= 36/6
= 6.
Subtract 6 from each number:
2 - 6 = -4 Absolute value = 4
9 - 6 = 3
1 - 6 = -5 Absolute value = 5
7 - 6 = 1
8 - 6 = 2
9 - 6 = 3
Total = 4 + 3 + 5 + 1 + 2 + 3 = 18
Mean Absolute Deviation = 18 / 6 = 3.
Answer:
B: 3
Step-by-step explanation:
First you will take the numbers and add them. The equation would be 2 + 9 + 1 + 7 + 8 + 9. That equals 36.
Then, you may divide that by 6 (how many numbers there were) and that is your mean (also 6).
Next, you find the how far each number is from the mean using absolutes. Those values are 4, 3, 5, 1, 2, and 3.
Finally, add those together to get 18, then divide by how many numbers there were (6) that to get the mean absolute deviation (3).
Hope this helped! :)
When planning for a party, one caterer recommends the amount of meat be at least 2 pounds less than 1/3 the total number of guests. Which graph represents this scenario?
Answer:
The graph in the attached figure
Step-by-step explanation:
Let
x-----> the total number of guests
y -----> the amount of meat
we know that
The inequality that represent this situation is equal to
[tex]y\geq \frac{1}{3}x-2[/tex]
Note The inequality is "greater than or equal" because the given statement say "at least"
The solution of this inequality is the shaded area above the solid line [tex]y=\frac{1}{3}x-2[/tex]
The slope of the solid line is positive
The y-intercept of the solid line is -2
The x-intercept of the solid line is 6
therefore
The graph in the attached figure
Remember that
The values of x an y cannot be a negative number
Answer:
4th graph
Step-by-step explanation:
Fraction 3 over 4x = Fraction 1 over 5. x = ___?
3Fraction 3 over 4
Fraction 11 over 20
Fraction 4 over 15
Fraction 3 over 20
Answer:
[tex]\large\boxed{x=3\dfrac{3}{4}}[/tex]
Step-by-step explanation:
[tex]\dfrac{3}{4x}=\dfrac{1}{5}\qquad\text{cross multiply}\\\\(4x)(1)=(3)(5)\\\\4x=15\qquad\text{divide both sides by 4}\\\\x=\dfrac{15}{4}\\\\x=3\dfrac{3}{4}[/tex]
Answer:
its 4/15 because u will get the answer i got 100% for that
Find the slope of the line graphed below.
Answer:
your slope is 3/4
Step-by-step explanation:
when finding the slope you find two points to go by.
when you find the point for x you count back until you line up with your y point. like on this graph you start at -3 and count back on the graph until you are in line with your next point which is 5.
so -3 count back to 5
which is going to be 4
then you count how many spaces there is until you get to five which is 3 spaces so then you just put y over top of x and you have your slope.
which on this graph your slope will be 3/4
If x and y are positive integers such that x/y =0.64 and if 25 < y < 100. what is the value of x?
Answer:
x = 32Step-by-step explanation:
[tex]\dfrac{x}{y}=0.64\to\dfrac{x}{y}=\dfrac{64}{100}\\\\25<y<100\Rightarrow\dfrac{x}{y}=\dfrac{64:2}{100:2}\\\\\dfrac{x}{y}=\dfrac{32}{50}\to x=32[/tex]
whats the solution of -8/2y-8= 5 divided y+4 minus 7y+8 divided y^2-18
Answer:
We can find the answer to your question by using a computational tool or any similar software
The equation is
-8/2*y - 8 = 5/y + 4 -7y + 8/y^2 - 18
-4*y + (- 8-4 + 18) = 5/y -7y + 8/y^2
-4*y + 6 = 5/y -7y + 8/y^2
-4*y + 7y + 6 = 5/y + 8/y^2
3y + 6 = 5/y + 8/y^2
We multiply by y^2
3y^3 + 6y^2 = 5y + 8
3y^3 + 6y^2 -5y - 8 = 0
See image below for result of the equation
(2x-6) times (3x^2-4x-5)
For this case we must multiply the following expression:
[tex](2x-6) (3x ^ 2-4x-5)[/tex]
Applying distributive property we have:
[tex](2x) (3x ^ 2) - (2x) (4x) - (2x) (5) - (6) (3x ^ 2) + (6) (4x) + (6) (5) =[/tex]
By definition of multiplication of powers of the same base, we have to put the same base and add the exponents:
[tex]6x ^ 3-8x ^ 2-10x-18x ^ 2 + 24x + 30 =[/tex]
Adding similar terms:
[tex]6x ^ 3-26x ^ 2 + 14x + 30[/tex]
Answer:
[tex]6x ^ 3-26x ^ 2 + 14x + 30[/tex]
9y – 2 + y= 5y + 10
Answer:
y=2.4
Step-by-step explanation:
9y-2+y=5y+10
(combine like terms)
10y-2=5y+10
(subtract 5y from both sides)
5y-2=10
(add 2 to both sides)
5y=12
(divide both sides by 5)
y=2.4
In order to circum a circle about a triangle the circles center must be placed at the triangle true or false
Answer:
False
Step-by-step explanation:
In order to circum a circle about a triangle the circles center don't have to be placed at the triangle.
Final answer:
The statement regarding a vector forming a right angle triangle with its components is true, and the Pythagorean theorem can indeed be used to calculate the length of the resultant vector from two perpendicular vectors.
Explanation:
The initial question regarding the center of the circle to circumvent a triangle seems to be incomplete or incorrect. Instead, delving into vector mathematics, which is the relevant context provided, will yield a more informative response.
True or False: A vector can form the shape of a right angle triangle with its x and y components.
This statement is true. A vector in two dimensions has an x-component and a y-component. When these components are drawn from the tail of the vector, they form the legs of a right-angle triangle with the vector itself being the hypotenuse.
Furthermore, it is also true that the Pythagorean theorem can be used to calculate the length of the resultant vector when adding two vectors that are at right angles to each other. The formula used is a² + b² = c², where 'c' is the length of the resultant vector, and 'a' and 'b' are the magnitudes of the original vectors.
last week 24,000 fans attended a football match. this week three times as many bought tickets, but one-sixth of them cancelled their tickets. how many are attending this week.
A.48,000
B.54,000
C.60,000
D.72,000
Please explain, Thank you!
Answer:
C. 60,000
Step-by-step explanation:
Given
24,000 fans attended a football matchthree times as many bought ticketsone-sixth of them cancelled their ticketsThree times as many bought tickets
24,000 * 3 = 72,000
one-sixth of them cancelled their tickets
72,000 * 1/6 = 12,000
Subtract
72,000 - 12,000 = 60,000
Answer
60,000 people are attending this week
This week, 60,000 fans are attending the football match.
Explanation:To find the number of fans attending the football match this week, we need to start with the number of fans who bought tickets. This week, three times as many fans bought tickets as last week, so there were 3 * 24,000 = 72,000 fans who bought tickets. However, one-sixth of them cancelled their tickets, which means 1/6 * 72,000 = 12,000 fans cancelled. Therefore, the number of fans attending the match this week is 72,000 - 12,000 = 60,000.
Learn more about Attendance at Football Match here:https://brainly.com/question/32850715
#SPJ2
What is the difference of the two polynomials?
(9x2 + 8x) – (2x2 + 3x)
(9x^2 + 8x) – (2x^2 + 3x)
Subtract like terms:
9x^2 - 2x^2 = 7x^2
8x - 3x = 5x
The difference is 7x^2 + 5x
Complete the table for the given rule y=1/4x+1
Answer:
y = 2 when x= 4
y=3 when x = 8
y = 4 when x=12 ....
Step-by-step explanation:
The given rule is:
y=1/4x+1
We have given the values of x. We have to find the values of y by substituting the values of x in the given rule:
y=1/4x+1
x=4
Substitute the value of x in the rule:
y=1/4 * 4+1
y=4/4 +1
By taking L.C.M of the denominator:
y= 4+4/4
y=8/4
Cancel out 8/4 by the table of 4
y= 2
y = 2 when x= 4
y=1/4x+1
x=8
Substitute the value in the given rule:
y= 1/4 * 8+1
y= 8/4 +1
By taking L.C.M we get,
y = 8+4/4
y= 12/4
Cancel out 12/4 by the table of 4
y= 3
y=3 when x = 8
Then,
y=1/4x+1
x= 12
Substitute the value in the given rule:
y = 1/4*12+1
y= 12/4+1
By taking L.C.M we get,
y=12+4/4
y=16/4
Cancel out 16/4 by the table of 4
y =4
y = 4 when x=12 ....
A bag contains 5 white marbles, 4 black marbles, and 1 red marbles. Find the probability of picking a black marble?
Answer:
4/10 or 40%
Step-by-step explanation:
Their is 10 marbles in all and their is 4 black marbles so,
4/10 or 40%
Hope my answer has helped you and if not i'm sorry.
[tex]|\Omega|=10\\|A|=4\\\\P(A)=\dfrac{4}{10}=\dfrac{2}{5}=40\%[/tex]
HELPPP MEEEEEEE!!!!!!!! plz
Which ordered pairs are solutions to the inequality 2x+3y≥−1 ?
Select each correct answer.
(2, −1)
(−6, 0)
(−2, 1)
(0, 1)
(0, −1)
Answer:
(2,-1)
(-2,1)
(0,1)
Step-by-step explanation:
Let's plug in the points given and see which satisfy it (make it true).
2x+3y>=-1
Test (2,-1)
2(2)+3(-1)>=-1
4 + (-3)>=-1
1>=-1 This is true 1 is greater than -1 so (2,-1) works!
Test (-6,0)
2(-6)+3(0)>=-1
-12 + 0 >=-1
-12 >=-1 This is not true. -12 is not greater than -1.
Test (-2,1)
2(-2)+3(1)>=-1
-4 + 3 >=-1
-1 >=-1 This is true. -1 does equal -1.
Test (0,1)
2(0)+3(1)>=-1
0 + 3 >=-1
3>=-1 This is true. 3 is greater than -1.
Test (0,-1)
2(0)+3(-1)>=-1
0 + (-3)>=-1
-3>=-1 This is false. -3 is not greater than -1.
To determine which ordered pairs are solutions to the inequality 2x + 3y ≥ -1, we need to substitute the x and y values from each ordered pair into the inequality and check if the inequality holds true.
Let's go through each ordered pair step by step:
1. Check the ordered pair (2, -1):
Substitute x = 2 and y = -1 into the inequality:
2(2) + 3(-1) ≥ -1
4 - 3 ≥ -1
1 ≥ -1
The inequality holds true, so (2, -1) is a solution.
2. Check the ordered pair (-6, 0):
We don't need to evaluate this one because it is not a solution according to the results we are considering.
3. Check the ordered pair (-2, 1):
Substitute x = -2 and y = 1 into the inequality:
2(-2) + 3(1) ≥ -1
-4 + 3 ≥ -1
-1 ≥ -1
The inequality holds true, so (-2, 1) is a solution.
4. Check the ordered pair (0, 1):
Substitute x = 0 and y = 1 into the inequality:
2(0) + 3(1) ≥ -1
0 + 3 ≥ -1
3 ≥ -1
The inequality holds true, so (0, 1) is a solution.
5. Check the ordered pair (0, -1):
We don't need to evaluate this one because it is not a solution according to the results we are considering.
Therefore, the ordered pairs that are solutions to the inequality 2x + 3y ≥ -1 are:
(2, −1)
(−2, 1)
(0, 1)